PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS MOBILE LEARNING MENGGUNAKAN ARTICULATE STORYLINE 3 KELAS X SMKN 1 KOTA SERANG - Dina Kamila; Yuni Maryuni (Universitas Negeri Malang, 2023)
The purpose of this development research is to describe procedure for developing learning media based on mobile learning in the study of national movement material for class X Vocational High School 1 Serang City, the second is to describe the results of the feasibility test for mobile learning-based learning media in the study of national movement material for class X Vocational High School 1 Serang City. The research method used is Research and Development (R&D) with reference to the (Walter & Gall D. Meredith, 1983) development model which simplifies the seven stages as follows: 1) Research and information collection, 2) Planning, 3) Develop preliminary form of product, 4 ) Preliminary field testing, 5) Main product revision, 6) Main field testing, 7) Operational product revision. The results of the feasibility of mobile learning-based learning media can be seen in the results of validation by a team of material experts, media and training as well as students' answers on limited product tests. This research shows that the mobile learning-based learning media can be used as an additional learning resource for students in history learning media with national movement material for class X Vocational High School 1 Serang.Tujuan dari penelitian pengembangan ini adalah untuk mendeskripsikan proses pengembangan media pembelajaran berbasis mobile learning pada kajian materi pergerakan nasional kelas X SMKN 1 Kota Serang, kedua mendeskripsikan hasil uji kelayakan Pembelajaran berbasis media mobile dalam ilmu pembahasan pergerakan nasional kelas X SMKN 1 Kota Serang. Metode penelitian yang digunakan yaitu Research and Development (R&D) dengan mengacu kepada model pengembangan (Walter & Gall D. Meredith, 1983) dimana didalamnya disederhanakan tujuh tahapan sebagai berikut: 1) Research and information collection, 2) Planning, 3) Develop preliminary form of product, 4) Preliminary field testing, 5) Main product revision, 6) Main field testing, 7) Operational product revision. Adapun hasil kelayakan media pembelajaran berbasis mobile learning dapat dilihat pada hasil validasi oleh tim ahli materi, media dan pelatihan serta jawaban peserta didik pada tes produk terbatas. Hasil penelitian media pembelajaran berbasis mobile learning dapat dijadikan sebagai sumber belajar tambahan bagi peserta didik pada media pembelajaran sejarah dengan materi pergerakan nasional kelas X SMKN 1 Kota Serang.